Low 25OH Vitamin D Blood Levels Are Independently Associated With Higher Amyotrophic Lateral Sclerosis Severity Scores: Results From a Prospective Study - Juntas-Morales, Raul; Pageot, Nicolas; Marin, Gregory; Dupuy, Anne-Marie; Alphandery, Sébastien; Labar, Laura; Esselin, Florence; Picot, Marie Christine; Camu, William (Frontiers in Neurology, 2020)
Background: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder characterized by progressive degeneration of upper and lower motor neurons. Prognosis is highly variable, ranging from few months to more than 30 years. 25OH vitamin D (25OH VD) blood levels have been associated with worse prognosis of ALS, but these results remain in dispute. We addressed this controversy with a prospective study and multivariate analysis to study the influence of known clinical prognostic factors of the disease and 25OH VD levels on Revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-R) severity score (ALS-SS), as defined by the monthly rate of decline of ALSFRS-R score, to identify the factors most closely linked to the risk of worsening of the disease. Results:This prospective cohort of ALS patients recruited 127 individuals, and 105 of them met inclusion criteria. Mean age of onset was 62.2 ± 12.1 years, 32% of subjects had bulbar onset, and gender ratio was 1.44 (male/female). Mean 25OH VD level was 26.8 ± 10.8 ng/ml and was similar between males and females. Patients with 25OH VD levels <15 ng/ml had significantly higher ALS-SS at inclusion (ALS-SSi) than those with normal levels (>30 ng/ml), p = 0.011. The study of ALS-SS as calculated at the end of follow-up (ALS-SSe) was not found correlated to initial 25OH VD levels (r = −0.19; p = 0.084). Univariate analysis showed that ALS-SSe correlated with 25OH VD levels, ALS duration at inclusion, slow vital capacity (SVC) at inclusion, and SVC loss. Multivariate model showed that 25OH VD levels were independently associated with ALS-SSe: r = −0.0125, p = 0.033. Log rank test with Kaplan–Meier curves did not show significant differences of survival between the groups defined by 25OH VD levels: <15, >15 and <30, and > 30 ng/ml, p = 0.88. Conclusions: This prospective study in ALS patients confirmed previous retrospective results: ALS-SSi is significantly higher in patients with severe VD deficiency. For the first time, multivariate analysis showed that 25OH VD level was an independent prognostic factor correlated to ALS-SSe, suggesting that discrepancies between previous works could be due to confounders. It would be important that the present work be replicated in larger samples to confirm the present findings.